Lithic Materials and Paleolithic Societies 2009
DOI: 10.1002/9781444311976.ch19
|View full text |Cite
|
Sign up to set email alerts
|

Raw Material Durability, Function, and Retouch in the Upper Paleolithic of the Transbaikal Region, Siberia

Abstract: Stone tool reduction intensity and raw material availability have often been correlated with human organizational strategies. Assemblages from Early, Middle, and Late Upper Paleolithic sites in the Transbaikal region of Siberia were compared and assessed for retouch amount using several techniques. These studies reveal that stone tool functional requirements play an important role in the amount and intensity of retouch in the region. It is also shown that artifact function correlates with raw material selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…This suggests that different lithic raw material types have different fracture properties and different amounts of brittleness and durability. Terry et al (2008) also found that raw material type tended to significantly vary with regard to different tool forms during the Upper Paleolithic in the Transbaikal region of Siberia. Thinking that these raw material differences might be related to raw material effectiveness for task completion, they established a set of experiments to test the effectiveness of scraping and cutting different densities of wood.…”
Section: Raw Materials and Organizational Choicesmentioning
confidence: 89%
See 2 more Smart Citations
“…This suggests that different lithic raw material types have different fracture properties and different amounts of brittleness and durability. Terry et al (2008) also found that raw material type tended to significantly vary with regard to different tool forms during the Upper Paleolithic in the Transbaikal region of Siberia. Thinking that these raw material differences might be related to raw material effectiveness for task completion, they established a set of experiments to test the effectiveness of scraping and cutting different densities of wood.…”
Section: Raw Materials and Organizational Choicesmentioning
confidence: 89%
“…Thinking that these raw material differences might be related to raw material effectiveness for task completion, they established a set of experiments to test the effectiveness of scraping and cutting different densities of wood. They found that extremely glassy cryptocrystalline chert was less effective for heavy-duty scraping than were more coarsely textured igneous rocks (Terry et al 2008). These results strongly suggest that lithic raw material types can be important for different functions and need to be considered in scenarios of technological organization.…”
Section: Raw Materials and Organizational Choicesmentioning
confidence: 93%
See 1 more Smart Citation
“…A few assemblages (Ust' Kova and Derbina 4/5) have bifacial projectile points (Akimova et al 2003;Goebel 2004b;Medvedev 1998b), whereas elsewhere most projectile points were constructed of osseous materials. Processing implements include simple retouched flakes and blades and a variety of other small, functional tools (Derevianko 2005;Graf 2008Graf , 2010Konstantinov 1994;Terry 2010;Terry, Andrefsky, and Konstantinov 2009).…”
Section: The Onset Of the Last Glacial Maximum: Middle Upper Paleolithicmentioning
confidence: 99%
“…All other macrotool types in the different occupations at the sites have relatively low frequencies. Some of the macrotool classes, particularly endscrapers and burins, are sometimes used in interpretations for specific activities such as hide scraping and engraving of bone and stone, respectively (Andrefsky, Jr., 2005;Terry et al, 2009;Hinguant et al, 2012;Clarkstone et al, 2015).…”
Section: Macrotoolsmentioning
confidence: 98%